Multi-Representation Discourse Learning Model As An Alternative Solution To Improve Student Learning Outcomes In Science Lessons - Abdul Rizal Ardiansyah (Jurnal Sekolah Dasar, 2021)
The purpose of this writing is to apply the Model of Multi-Representation Discourse Learning Model as an Alternative Solution to Improve Student Learning Outcomes in Science Subjects. The subject in this writing is grade 4 students at SD Islam Putradarma Tambun Selatan. The author found some facts of problems in the observation, when viewed from the daily replay of the students' science, from the number of 45 out of 2 classes and only 10 students who were able to achieve the KKM score. The author uses the Multi Representation Discourse Model as one of the solutions to improve the learning process of previous students' science.The Multi Representation Discourse Model is a lesson designed by teachers in order to generate discussion through problem presentation, assignments, and student training. this learning students communicate unofficially so that students are able to express ideas casually according to their own language.so that students can be more active in the learning process. Predicted results with multi-representation (DMR) discursion learning model can improve learning outcomes. There is an influence of multi-representation discursion learning model on student learning outcomes, with indicators of cognitive learning outcomes C1 (Knowledge). C2 (Understanding), C3 (Application), C4 (Analysis), C5 (Synthesis), C6 (Evaluation). In the process of teaching and learning, this cognitive aspect is the most prominent and can be seen directly from the test results.